Transforming the Jatayu Symbol into Contemporary Typeface Design: A Practice-Based Approach - Dewi, I Gusti Agung Ayu Alicia Pradnya; Pitriani, I Gusti Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This study examines the visual transformation of the Jatayu symbol in contemporary typeface design as an effort to translate cultural symbols into a communicative and character-driven letterform system. Jatayu was selected because of its strong symbolic meaning as a representation of bravery, sacrifice, loyalty, and struggle, as well as its rich visual potential for typographic development. The study responds to the limited integration of cultural symbols into typographic systems, as culture-based design practices often remain at a decorative level rather than being conceptually and structurally embedded in letterform design. It aims to explain how a cultural symbol can be transformed into a coherent and communicative typeface with conceptual legitimacy in contemporary design practice. This research employs a qualitative descriptive approach with a practice-based design orientation. Data were collected through document study, visual observation, and artifact analysis of the “Jatayu” typeface and were analyzed using descriptive visual analysis. The findings show that the Jatayu symbol, particularly its wing element, was transformed through formal abstraction into pointed accents, dynamic curves, and rhythmic strokes that construct a heroic, firm, and elegant visual character while maintaining readability and systemic consistency.